Odłączenie naczyniówki – patogeneza, przyczyny i obraz kliniczny - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Serous choroidal detachment is characterized by exudative detachment of the retina and choroid following leakage of fluid from the choriocapillaris into suprachoroidal space. This accumulation of fluid has been known to be a complication of various intraocular surgeries (cataract, glaucoma and retinal detachment surgery), where hypotony is combined with postoperative inflammation. Among other non surgical conditions associated with uveal effusion are idiopathic (uveal effusion syndrome, microphthalmia) and inflammatory diseases (scleritis, sympathic ophthalmia, pars planitis, Harada’s disease). Idiopathic serous detachment of choroids is caused by scleral abnormalities associated with hypoplasia or partial absence of the vortex venous system. The most cases of postoperative choroidal detachment resolve spontaneously. Resolution is usually associated with rapid normalization of the intraocular pressure and reduction of intraocular inflammation. The natural course of idiopathic condition is variable but tends to be prolonged with remissions and exacerbations. Surgical management involving vortex vein decompression and/or sclerotomy is the most effective treatment in this patients.